2014
DOI: 10.1002/star.201400068
|View full text |Cite
|
Sign up to set email alerts
|

In vitro inhibitory effects of Sardinian Pistacia lentiscus L. and Pistacia terebinthus L. on metabolic enzymes: Pancreatic lipase, α‐amylase, and α‐glucosidase

Abstract: Pancreatic triacylglycerol lipase (PL), α‐amylase, and α‐glucosidase are appealing pharmacological targets for the management of dyslipidemia, atherosclerosis, and obesity‐diabetes. Presently, in vitro screening for considerable inhibition of these digestive hydrolases by endemic Sardinian Pistacia lentiscus L. and P. terebinthus L. leaves and fruits aqueous extracts (AEs) (Anacardiaceae) was undertaken. The AEs PL‐IC50 (µg/mL) in an ascending order were: P. lentiscus leaves; 6.1 ± 0.2 Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 45 publications
1
19
0
Order By: Relevance
“…Thus, in agreement with the fragmentation patterns described in the literature [62,64] High contents of gallotannins (galloylquinic acid derivatives) and myricetin derivatives were previously described in P. letiscus leaves [6,7,9,17,68]. These compounds represent approximately 90% of the polyphenolic composition of the leaf extracts [6] and are possibly the main responsible for their biological properties such as: anti-inflammatory, cytoprotective, hepatoprotective, enzymatic-inhibitory, antitumor, and anti-diabetes [7,62,[69][70][71]. It is noteworthy that the two molecules here tentatively identified as tetragalloylquinic acid derivatives have not been described yet in lentisk leaves.…”
Section: Polyphenolic Composition Of the Richest P Lentiscus Extractsupporting
confidence: 85%
“…Thus, in agreement with the fragmentation patterns described in the literature [62,64] High contents of gallotannins (galloylquinic acid derivatives) and myricetin derivatives were previously described in P. letiscus leaves [6,7,9,17,68]. These compounds represent approximately 90% of the polyphenolic composition of the leaf extracts [6] and are possibly the main responsible for their biological properties such as: anti-inflammatory, cytoprotective, hepatoprotective, enzymatic-inhibitory, antitumor, and anti-diabetes [7,62,[69][70][71]. It is noteworthy that the two molecules here tentatively identified as tetragalloylquinic acid derivatives have not been described yet in lentisk leaves.…”
Section: Polyphenolic Composition Of the Richest P Lentiscus Extractsupporting
confidence: 85%
“…Pistacia lentiscus and P. terebinthus leaf and fruit aqueous extracts were observed to inhibit α-amylase and α-glucosidase enzymes with IC 50 values ranging from 65.3 ± 7.4 µg/mL to 1.4 ± 0.2 mg/mL, respectively. The findings of the study exerted that Sardinian Pistacia species can be used as functional foods and nutraceuticals that modulate carbohydrate and lipid digestion and absorption as potential sources to prevent obesity and diabetes mellitus (37).…”
Section: Discussionmentioning
confidence: 97%
“…This result was confirmed by in vitro tests for the inhibition of α-amylase [ 44 ]. Further investigations confirmed that aqueous extracts of the leaves were identified as strong and effective dual inhibitors of α-amylase and glucosidase in vitro [ 52 ].…”
Section: Other Activitiesmentioning
confidence: 97%